Evaluation of etiology of discoloration, site of discoloured tooth and outcomes of different techniques used for vital tooth bleaching- a retrospective analysis - DESHMUKH, MADHURA; AHMED, NABEEL (The journal of contemporary issues in business and government, 2020)
Smile is a curve that sets everything straight but a healthy smile needs good dental care.The appearance of the dentition is paramount to a large population seeking dental treatment and often the first evidence of variation from normal in human dentition is an observable difference in the color of the teeth.A thorough knowledge of the etiology of tooth staining is of prime importance to dental practitioners in order to reach a correct diagnosis.. The purpose of this study was to assess the etiology, discoloured surfaces and outcomes of different techniques in terms of patient satisfaction for the management of vital bleaching. A total of 31 case sheets were retrospectively analysed from the university database. It was found that Fluorosis was the most prevalent etiology in about 74.19%, Conventional technique was the most prevalent technique in about 83.87% and Upper anteriors were the most prevalent affected area in about 70.97%. It was also found that in both 16-25 yrs and 26-45 yrs age groups, fluorosis was the most prevalent etiology. In 46+yrs, both fluorosis and stains were equally prevalent, p value-0.102 (p>0.05). It was found that fluorosis was the prevalent etiology in both males(64.52%) and females(9.68%), p-value: 0.395 (p>0.05). For all sites, conventional technique is the most prefered technique, p-value: 0.751(p>0.05). The outcome for both Conventional and Power bleach techniques had prevalence of satisfaction, p-value: 0.342(p>0.05). Within the limitations of the study, we conclude that fluorosis was the most prevalent etiology for vital tooth discolouration. The discolouration of vital teeth was commonly presented in the upper anterior area followed by both upper and lower anteriors. Outcomes for conventional technique were more satisfactory than thermocatalytic.